1984
DOI: 10.1115/1.3242405
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Verification of Laser-Velocimeter Sampling Bias and Its Correction

Abstract: The existence of “sampling bias” in individual-realization laser velocimeter measurements is experimentally verified and shown to be independent of sample rate. The experiments were performed in a simple two-stream mixing shear flow with the standard for comparison being laser-velocimeter results obtained under continuous-wave conditions. It is also demonstrated that the errors resulting from sampling bias can be removed by a proper interpretation of the sampling statistics. In addition, data obtained in a sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…The statistical prediction and the corrected results are in good agreement up to 40% intensity levels. The low speed data of Johnson et al (1982) are similar. The turbulence intensity based on the local mean velocity magnitude was 30%-35% at y* =0, the middle of the mixing layer.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…The statistical prediction and the corrected results are in good agreement up to 40% intensity levels. The low speed data of Johnson et al (1982) are similar. The turbulence intensity based on the local mean velocity magnitude was 30%-35% at y* =0, the middle of the mixing layer.…”
Section: Resultssupporting
confidence: 55%
“…The reduction of the bias between free running and processor controlled sampling has been observed experimentally, see Johnson et al (1982), Craig et al (1984), and Stevenson et al (1982), and it appears that if the sampling rate is on the order of 50 times less than the validated particle data rate, the data is unbiased. Conversely, the mean validated particle data rate must be significantly smaller than the processor sampling rate for the data to be completely biased.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…This validation rate was high enough to permit eliminating velocity bias by inhibiting the counter processors for a fixed time interval between samples, approximating equal time sampling. This method has previously been described by Stevenson et al 11 and its effectiveness confirmed in subsequent studies, including the work by Gould et al, 9 Durrett et al, 10 Johnson et al, 12 and Gouldet al 13 …”
Section: Flow Systemmentioning
confidence: 66%
“…This ''bias'' was eliminated from the measurements by a post-processing step, proposed by Pandey et al (2004), where multiple recordings by the same particle were discarded. The second kind of ''velocity bias'' associated with LDV measurements is associated with long measurement times (Johnson et al, 1983). To minimize this bias, the velocity measurements were done for a short span.…”
Section: Resultsmentioning
confidence: 99%